"Проектный офис": методология создания информационное издание - Сорокин П. П. Павел Павлович; Кирянов Е. Л. Евгений Львович; Стрюков А. В. Артем Владимирович; Рукавишников В. С. Валерий Сергеевич (Томск, Изд-во ТПУ, 2024)
Заглавие с титульного экрана